2019
DOI: 10.3390/w11081614
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Effect on Growth of Artemia franciscana Exposed to Two Common Organic Pollutants

Abstract: Acute toxicity and inhibition on growth of Artemia franciscana nauplii (Instar I-II) after exposure to the reference toxicants bisphenol a (BPA) and sodium dodecyl sulfate (SDS) were studied. LC 50 values were calculated and differences in body growth were recorded after 24, 48, and 72 h of exposure to the toxicants. The results indicated that BPA had lower toxicity than SDS. Development of the nauplii was clearly influenced by duration of exposure. Growth inhibition was detected for both toxicants. Abnormal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Brine shrimp Artemia is a fi lter-feeding zooplankton that can adapt to a wide salinity range. It has some virtues such as shorter life cycle, bigger off spring number per brood, and easy to handle in the laboratory (Lavens and Sorgeloos, 1996), and thus has been widely used as a test organism for ecotoxicology study (Manfra et al, 2015;Vannuccini et al, 2015;Ekonomou et al, 2019). Nowadays, Artemia are increasingly used as test organisms for marine ecotoxicology study, with special focus on the toxicity of micro-and nano-particles on Artemia growth, morphology and physiology properties (Rodd et al, 2014;Bergami et al, 2017;Minetto et al, 2017;Rotini et al, 2018;Sarkheil et al, 2018;Varó et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Brine shrimp Artemia is a fi lter-feeding zooplankton that can adapt to a wide salinity range. It has some virtues such as shorter life cycle, bigger off spring number per brood, and easy to handle in the laboratory (Lavens and Sorgeloos, 1996), and thus has been widely used as a test organism for ecotoxicology study (Manfra et al, 2015;Vannuccini et al, 2015;Ekonomou et al, 2019). Nowadays, Artemia are increasingly used as test organisms for marine ecotoxicology study, with special focus on the toxicity of micro-and nano-particles on Artemia growth, morphology and physiology properties (Rodd et al, 2014;Bergami et al, 2017;Minetto et al, 2017;Rotini et al, 2018;Sarkheil et al, 2018;Varó et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bisphenol A toxicity has been studied extensively in the literature. Economou et al [ 37 ] found that the mean values of LC 50 were 45.51 mg dm −3 for A. franciscana . The LC 50 , EC 50 , and IC 50 values of BPA reported previously for other aquatic organisms vary between 4.6 to 17.93 mg dm −3 for fish and 0.3 to 10 mg dm −3 for invertebrate species [ 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…After 48 h, the organisms in each test tube were analyzed, and the living and dead were counted. The survivors were fixed in tamponed formaldehyde and analyzed under microscope (Leica Ⓒ -model M2005C) for measuring the body lengths and other morphological deformities, according to Ekonomou et al (2019).…”
Section: Methodsmentioning
confidence: 99%